2019
DOI: 10.1097/meg.0000000000001270
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of hepatocellular carcinoma and postoperative complications in patients with nonalcoholic steatohepatitis as a primary indication for deceased liver transplantation

Abstract: Background and aims Nonalcoholic steatohepatitis (NASH) is an increasingly prevalent indication for liver transplantation (LT) across the world. The relative outcomes following transplantation are poorly described in this cohort. We aimed to analyze the incidence and outcome of LT for NASH as compared with other indications. Patients and methods This is a retrospective analysis of 513 patients who underwent deceased-donor, adult LT between 2002 and 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…Major morbidity rates were comparable in HCC patients with cirrhosis, who received maEDC and no-maEDC grafts, and transplanting grafts with ≥1 maEDC bore no risk for early allograft dysfunction, primary nonfunction, or 30-day graft failure in these recipients. The morbidity and retransplant rates are comparable with those already reported [39,40,41]. Grafts with ≥1 maEDC were associated with a reduced short-term graft survival, but they did not affect one-year patient survival and one-year patient survival after censoring for death with functioning graft.…”
Section: Discussionsupporting
confidence: 85%
“…Major morbidity rates were comparable in HCC patients with cirrhosis, who received maEDC and no-maEDC grafts, and transplanting grafts with ≥1 maEDC bore no risk for early allograft dysfunction, primary nonfunction, or 30-day graft failure in these recipients. The morbidity and retransplant rates are comparable with those already reported [39,40,41]. Grafts with ≥1 maEDC were associated with a reduced short-term graft survival, but they did not affect one-year patient survival and one-year patient survival after censoring for death with functioning graft.…”
Section: Discussionsupporting
confidence: 85%
“…The shortand long-term results examined in various studies was similar between NAFLD/NASH and non-NAFLD/NASH, including alcoholic liver disease, HBV, cryptogenic cirrhosis, and primary biliary cholangitis/primary sclerosing cholangitis (PBC/PSC). Remarkably, overall survival showed no significant difference [77,78,[86][87][88][89][90]. Interestingly, post-transplant survival was shown to be higher compared with HCV-associated LT whereas no difference was seen between NASH-associated and alcoholic liver disease-related LT [90,91].…”
Section: Outcome Of Liver Transplantation In Nafld/nash Patientsmentioning
confidence: 95%
“…When comparing the results of HCC related LT, no difference was found between NASH-and non-NASH-associated HCC-related LT. Rather, there was a trend towards a favorable outcome for NASH-associated HCC-related LT [87,89]. The prevalence of HCC in NASH-associated LT was higher compared with non-NASH-associated LT [78,87,88]. Interestingly, when subclassifying non-NASH-associated HCC on explant pathology, Agopian et al showed a significantly higher prevalence of HCC in recipients with HCV and HBV, a similar prevalence in recipients with alcoholic liver disease and a lower prevalence in recipients with PBC/ PSC when comparing with recipients with NASH [90].…”
Section: Outcome Of Liver Transplantation In Nafld/nash Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study involving 588 liver transplant recipients, of which 9.4% were transplanted for NASH, post-transplant allograft steatosis was not associated with post-transplant survival (28). Although studies have shown worse outcomes with patients being transplanted NASH related HCC as well as patients being re-transplanted for NASH, no such data exists with NASH recurrence post-transplant (28)(29)(30). Hence, till further prospective data is generated it would be prudent to assume that survival is not influenced by recurrence of NASH.…”
Section: The Implication Of Recurrent Nafld On Posttransplant Survivalmentioning
confidence: 99%